2019
DOI: 10.1111/dar.13004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the limit of detection of Fourier‐transform infrared spectroscopy and immunoassay strips for fentanyl in a real‐world setting

Abstract: Introduction and AimsDrug checking is a harm reduction intervention increasingly used in the context of the opioid overdose epidemic. The aim of the study was to determine the limit of detection for fentanyl of two point‐of‐care drug checking technologies.Design and MethodsSamples tested at point‐of‐care using Bruker Fourier transform infrared (FTIR) spectroscopy and BTNX fentanyl immunoassay strips were sent for confirmatory laboratory analysis using quantitative nuclear magnetic resonance (qNMR) spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 10 publications
1
70
0
Order By: Relevance
“…The crystal is cleaned with isopropanol and a new baseline is collected prior to each sample measurement. Although the limit of detection (LOD) for specific components in a drug mixture is difficult to assess due to the variety of cutting agents present, moisture content of the sample, and scattering effects due to power particle size, studies have estimated the LOD for fentanyl using IR spectroscopy to be in the range 1%–5% by weight 31,33 …”
Section: Instruments and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystal is cleaned with isopropanol and a new baseline is collected prior to each sample measurement. Although the limit of detection (LOD) for specific components in a drug mixture is difficult to assess due to the variety of cutting agents present, moisture content of the sample, and scattering effects due to power particle size, studies have estimated the LOD for fentanyl using IR spectroscopy to be in the range 1%–5% by weight 31,33 …”
Section: Instruments and Measurementsmentioning
confidence: 99%
“…In Toronto, Canada, drug checking is being piloted within several supervised injection sites with samples tested using fentanyl immunoassay test strips onsite and testing samples offsite using LC‐ and GCMS techniques 32 . Also in Canada, the British Columbia Centre on Substance Use is piloting point‐of‐contact drug checking at multiple supervised injection sites and overdose prevention sites using a Fourier transform infrared spectroscopy with test strips 27,33 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These systems have modest power requirements, are relatively low cost, and have rapid analysis times. An assessment of FTIR spectroscopy and immunoassay test strips for the analysis of fentanyl in real street drug samples found that of 173 samples that tested positive for fentanyl (using quantitative nuclear magnetic resonance), 30 (17.3%) failed to detect fentanyl using FTIR spectroscopy, and four (2.3%) did not detect fentanyl using immunoassay test strips 8 . FTIR was able to quantify drug and excipient content, but required concentrations ≥10% w/w, and even the immunoassay test strips required fentanyl concentrations ≥5% w/w for reliable detection.…”
Section: Introductionmentioning
confidence: 99%
“…(15,16) In order to help prevent overdoses, lateral ow immunoassay test strips originally designed for monitoring traces of fentanyl and its analogs in urine are being explored as a drug checking technology in harm reduction contexts. (17)(18)(19)(20) One commonly used fentanyl test strip or "FTS" (BTNX Inc., Markham, ON, Canada) is a lateral ow chromatographic immunoassay for the qualitative detection of fentanyl in urine at the cutoff concentration of 20 ng/ml. A positive result on this test strip gives one line, a negative result gives two lines, and an invalid test gives either no line or no control line.…”
Section: Introductionmentioning
confidence: 99%